(untitled) (Fiep Bulletin - online, 2016)
This paper aims to present and illustrate how the image of women has been used for decades by Brazilian advertising. Although women have come out of a subordinate position in which her fate was decided by the man - her father, and later her husband - to occupy different spaces in society, the way her body image is portrayed in Brazilian ads does not changed completely. Advertising has always made use of the female image. The incipient beginning of advertising in Brazil, when there was still a concern about textual techniques, about the correct use of the image and the definition of a concept that would provide a good product sale, the woman’s body has appeared in ads. If only figuratively, it was part of the image related to the product. With time and with the change of woman’s role in society, it was revealed that she was the official buyer of the family, making it also a direct consumer. In this sense, the woman has always been the target of various types of campaigns. However, it continues to be portrayed basically in two ways: as a sexual object and linked to household chores. To prove this statement, we will analyze the image and the text of three ads from the 1950s and three current ads. The analysis is based on the Aristotelian model of speech.